The performance of labyrinth weirs - Taylor, Geoffrey (1968)
The purpose of the labyrinth weir is to increase the discharge per unit length of structure normally obtained from a conventional weir when operating under identical head conditions. This is achieved by compressing a large length of crest in concertina form, into the space available on site.